Tollip deficiency exaggerates airway type 2 inflammation in mice exposed to allergen and influenza A virus: role of the ATP/IL-33 signaling axis - Nouri, Hamid Reza; Schaunaman, Niccolette; Kraft, Monica; Li, Liwu; Numata, Mari; Chu, Hong Wei (Frontiers in Immunology, 2023)
Toll-interacting protein (Tollip) is a negative regulator of the pro-inflammatory response to viruses, including influenza A virus (IAV). Genetic variation of Tollip has been associated with reduced airway epithelial Tollip expression and poor lung function in patients with asthma. Whether Tollip deficiency exaggerates type 2 inflammation (e.g., eosinophils) and viral infection in asthma remains unclear. We sought to address this critical, but unanswered question by using a Tollip deficient mouse asthma model with IAV infection. Further, we determined the underlying mechanisms by focusing on the role of the ATP/IL-33 signaling axis. Wild-type and Tollip KO mice were intranasally exposed to house dust mite (HDM) and IAV with or without inhibitors for IL-33 (i.e., soluble ST2, an IL-33 decoy receptor) and ATP signaling (i.e., an antagonist of the ATP receptor P2Y13). Tollip deficiency amplified airway type 2 inflammation (eosinophils, IL-5, IL-13 and mucins), and the release of ATP and IL-33. Blocking ATP receptor P2Y13 decreased IL-33 release during IAV infection in HDM-challenged Tollip KO mice. Furthermore, soluble ST2 attenuated airway eosinophilic inflammation in Tollip KO mice treated with HDM and IAV. HDM challenges decreased lung viral load in wild-type mice, but Tollip deficiency reduced the protective effects of HDM challenges on viral load. Our data suggests that during IAV infection, Tollip deficiency amplified type 2 inflammation and delayed viral clearance, in part by promoting ATP signaling and subsequent IL-33 release. Our findings may provide several therapeutic targets, including ATP and IL-33 signaling inhibition for attenuating excessive airway type 2 inflammation in human subjects with Tollip deficiency and IAV infection.